Galanin ameliorates liver inflammation and fibrosis in mice by activating AMPK/ACC signaling and modifying macrophage inflammatory phenotype - He, Lingnan; Huang, Chao; Wang, Hui; Yang, Naibin; Zhang, Jianbin; Xu, Leiming; Gu, Ting; Li, Zhenghong; Chen, Yuanwen (Frontiers in Immunology, 2023)
Background and aims Galanin is a naturally occurring peptide that plays a critical role in regulating inflammation and energy metabolism, with expression in the liver. The exact involvement of galanin in non-alcoholic fatty liver disease and related fibrosis remains controversial. Methods The effects of subcutaneously administered galanin were studied in mice with non-alcoholic steatohepatitis (NASH) induced by a high-fat and high-cholesterol diet for 8 weeks, and in mice with liver fibrosis induced by CCl4 for 7 weeks. The underlying mechanism was also studied in vitro on murine macrophage cells (J774A.1 and RAW264.7). Results Galanin reduced inflammation, CD68-positive cell count, MCP-1 level, and mRNA levels of inflammation-related genes in the liver of NASH mice. It also mitigated liver injury and fibrosis caused by CCl4. In vitro, galanin had anti-inflammatory effects on murine macrophages, including reduced phagocytosis and intracellular reactive oxygen species (ROS). Galanin also activated AMP-activated protein kinase (AMPK)/acetyl-CoA carboxylase (ACC) signaling. Conclusion Galanin ameliorates liver inflammation and fibrosis in mice, potentially by modifying macrophage inflammatory phenotype and activating AMPK/ACC signaling.